2007
DOI: 10.1002/esp.1504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbiotic crusts under cropland in temperate environments on soil erodibility during concentrated flow

Abstract: Several studies illustrate the wind and water erosion‐reducing potential of semi‐permanent microbiotic soil crusts in arid and semi‐arid desert environments. In contrast, little is hitherto known on these biological crusts on cropland soils in temperate environments where they are annually destroyed by tillage and quickly regenerate thereafter. This study attempts to fill the research gap through (a) a field survey assessing the occurrence of biological soil crusts on loess‐derived soils in central Belgium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 54 publications
1
64
1
1
Order By: Relevance
“…Subsequent rain events have only a minor effect on Kc (Knapen et al, 2008b). Later in the growing season, when a dense root network has developed and microbiotic crusts appear on many sealed soil surfaces in the Belgian loess belt, Kc will further decrease (Knapen et al, 2007c). However, soil water content changes have a large impact on Kc and may mask the decreasing trend in Kc.…”
Section: Soil Property Effects On Sermentioning
confidence: 90%
See 2 more Smart Citations
“…Subsequent rain events have only a minor effect on Kc (Knapen et al, 2008b). Later in the growing season, when a dense root network has developed and microbiotic crusts appear on many sealed soil surfaces in the Belgian loess belt, Kc will further decrease (Knapen et al, 2007c). However, soil water content changes have a large impact on Kc and may mask the decreasing trend in Kc.…”
Section: Soil Property Effects On Sermentioning
confidence: 90%
“…89, ME = 0 . 78, n = 171), when data of several studies (Knapen, 2007;Knapen et al, 2007bKnapen et al, , 2007cKnapen et al, , 2008aKnapen et al, , 2008b) are combined, is shown in Figure 1. ME is the model effi ciency as defi ned by Nash and Sutcliffe (1970).…”
Section: Soil Property Effects On Sermentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, although runoff was measured in tropical (Valentin and d'Herbès, 1999;van de Giesen et al, 2000), humid (Rutin, 1983;Jungerius and ten Harkel, 1994), temperate (Bergkamp et al, 1999;Knapen et al, 2007), and arid and semi-arid zones (Booth, 1941;Bergkamp et al, 1996;Li et al, 2008), the role of MCs as impacting surface hydrology is not yet clear (Eldridge, 2001;Warren, 2001a). Whereas some researchers observed that MCs promote runoff (Loope and Gifford, 1972;Brotherson and Rushforth, 1983;Graetz and Tongway, 1986;Kidron and Yair, 1997;Kidron et al, 2003), others maintained that MCs impede runoff (Finlayson et al, 1987;Harper and Marble, 1988;Greene and Tongway, 1989;Alexander and Calvo, 1990;Williams et al, 1995Williams et al, , 1999.…”
Section: Introductionmentioning
confidence: 90%
“…Runoff generation on sandy soils may, however, take place following the establishment of a MC (Eldridge, 2001;Warren, 2001b;Kidron, 2007). While a PC may precede the establishment of a MC (Bowker, 2007;Knapen et al, 2007), the presence of a MC has been seen as essential for runoff generation on sand (Kidron, 1999).…”
Section: Introductionmentioning
confidence: 98%